Application of the Ultimum Remedium Principle to Environmental Crimes in Indonesia - Frenki Hamonangan Turnip; Rahmayanti Rahmayanti; Suci Ramadani (Journal of Research in Social Science and Humanities, 2025)
The principle of ultimum remedium in environmental criminal law is a principle that places criminal sanctions as the last resort after administrative and civil sanctions are no longer effective. This principle aims to ensure that environmental law enforcement proceeds proportionally and not repressively. However, in practice in Indonesia, the application of the ultimum remedium principle often creates a dilemma between environmental protection and economic development interests. Many environmental violations such as forest fires, river pollution, and illegal mining activities are resolved only through administrative measures without criminal sanctions, even though the resulting damage is highly significant. This study employs a normative juridical method with statutory, conceptual, and case approaches to analyze the extent to which the implementation of the ultimum remedium principle can uphold ecological justice. The research findings show that the application of this principle in Indonesia tends to be weak, as many environmental violations are not prosecuted criminally under the pretext of efficiency and economic stability. In fact, environmental criminal law plays a crucial role as a deterrent instrument against environmental crimes. Therefore, environmental law reform in Indonesia needs to be directed toward strengthening criminal law enforcement against offenders—especially corporations responsible for large-scale environmental damage.